Неоткрытый Рим: История. Легенды. Предания - Бурлак Вадим (Тайны знаменитых городов, 2009)
Экземпляры: БС (20170220) / Инвентарный номер: РТШ51518 / Сис.шифр: 63.3(0) / Авт.знак: Б 91 / ГРНТИ: 03 / ББК: 63.3(0)32